Relationship Between Nurse Management Functions And Work Functions Of Implementing Nurses In Non-Surgery Inpatient Efarina Etaham Hospital - Awaluddin Ziad; Chrismis Novalinda Ginting; Masryna Siagian (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Nurses play an important role in the administration of nursing services because nurses are the main key to the organization. However, there are still many roles and functions of nurses that have not been going well. The aim of this research is to determine the relationship between the management function of nurses and the work function of executive nurses in non-surgical inpatient care at Efarina Etaham Hospital. Type of quantitative research with a cross sectional approach. The study sample was 66 executive nurses in a non-surgical inpatient hospital at Efarina Etaham Hospital. The data was analyzed using the Spearmen's Rank test. The results of the study showed that there was a significant relationship between the management function of nurses and the work function of executive nurses in non-surgical inpatient care at Efarina Etaham Hospital, p value = 0.000. The level of strength of the relationship between the variables Nurse Management Function and Executive Nurse Work Function is 0.716 or strong. The results of this research can be used as a source of information and analytical reports that can be useful for hospital management in terms of improving nurses' work functions. The results of this research are used as input and consideration for Efarina Etaham Hospital in making decisions, especially in addressing management function issues so that Efarina Etaham Hospital continues to develop and can carry out management functions well. Future research should direct research with a larger survey scope with more in-depth interviews or experiments and with a larger sample, so that the causal factors can be identified. Keyword: Function management, Nurse work